ANALISIS PENERIMAAN DAN EFEKTIVITAS RETRIBUSI TERMINAL TERHADAP PENDAPATAN ASLI DAERAH DI KOTA AMBON TAHUN 2014-2018 - Dwi Kriswantini (Soso-Q : Jurnal Manajemen, 2021)
Abstract:This study, aims to determine the growth of terminal user fees from 2014 to 2018, the  effectiveness  of  terminal  user  fees  from  2014  to  2018,  the  contribution  of terminal  user  fees.  Secondary  data  type,  data  source  from  the  Department  of Transportation  and  the  Ambon  City  Revenue  Office.  Data  collection  techniques through  documentation.  Analysis  of  the  data  used  is  the  analysis  of  growth, effectiveness and contribution. The results of data analysis show that (1) the growth of revenue from parking fees in  Ambon  City  in  2015  was  (10.43%);  in  2016  amounted  to  3.82%;  in  2017 24.82%; this means that growth is positive while in 2018 the growth is negative at only  0.53%.  (2)  The  effectiveness  of  station  retribution  receipts  in  Ambon  City from  2014  to  2018  reached  an  average  of  87.75%  per  year.  This  shows  that  the acceptance  of  Station  charges  in  Ambon  city  is  not  effective.  (2)  Contribution  of Station Retribution Receipts to Regional Original Revenues amounted to 3.03% in 2014; 2.34% in 2015; 2.31% in 2016; 2.59% in 2017, while in 2018 there was a decrease of 0.24% to 2.35% from 2017.  Keywords: Reception, Effectiveness, Retribution, Region Original Income